Design and Analysis of A New Check Valve on Water Hammer Performance by using Solid Work Flow Simulation - Mat Supri, Iskandar Mukhriz; Madon, Rais Hanizam; Mohd Salleh, Zuliazura; Madon, Hariyani (Progress in Engineering Application and Technology, 2021)
Basically, a check valve permits stream one way and naturally forestalls reverse (turn around stream) during a liquid in the line inverts heading. These check valves consist of an openings disc and two-port valves, purposely for the liquid to enter and leave. Water hammer occurs in check valves, involves the jack forces on the disc and it happens during the disc is shut while the fluid still flows into the valves. This phenomenon had triggers feared as violent damage to the disc of check valves by creating a hammering sound and increase the wear and tear rate onto the disc. This study is conducted to find the optimum design to reduce the water hammer impact on the disc. In this study, three new design disc is introduced whereby the analysis and performance were validated by a simulation through SolidWorks Flow Simulation. Steady-state water flows with an inlet velocity of 2 m/s, 1 bar gauge pressure, opening angle 0°, 22.5°, 45° and 67.5° were specified as the boundary condition. The hydrodynamic, torque and velocity acting in the valve were applied as the critical parameter and used to select the best disc design. From this research, the contour analysis for pressure and velocity for standard and design 2 shows a better result in terms of uniform flow distributions. Based on all critical parameters, disc 3 shows the lowest performance among all the check valves. This is due to pressure and velocity drop in almost all angles of the opening disc. Design 2 satisfy the optimum performance at boundary condition of pressure, velocity and hydrodynamic. In this framework, check valve design 2 shows the increment of performance in terms of velocity and pressure distribution in the check valve compared to the other check valves.